2010
DOI: 10.1126/science.1183415
|View full text |Cite
|
Sign up to set email alerts
|

The Onset of Collective Behavior in Social Amoebae

Abstract: In the social amoebae Dictyostelium discoideum, periodic synthesis and release of extracellular cyclic AMP (cAMP) guides cell aggregation and commitment to form fruiting bodies. It is unclear whether these oscillations represent an intrinsic property of individual cells or if they only exist as a population-level phenomenon. Here we show by live-cell imaging of intact cell populations that pulses originate from a discrete location despite constant exchange of cells to and from the region. In a perfusion chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
436
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(460 citation statements)
references
References 29 publications
23
436
1
Order By: Relevance
“…These processes have been modelled to a great extent and the main features are understood in some considerable detail [32,[81][82][83][84][85][86] ( figure 10). Initially, the cAMP waves were measured in fixed time points using an ingenious isotope dilution strategy, but more recently it has been possible to measure the cAMP waves dynamically using dedicated FRET constructs [87,88]. Interesting questions that can now be started to be resolved are what is the exact mechanism of cAMP amplification in single cells?…”
Section: Aggregationmentioning
confidence: 99%
“…These processes have been modelled to a great extent and the main features are understood in some considerable detail [32,[81][82][83][84][85][86] ( figure 10). Initially, the cAMP waves were measured in fixed time points using an ingenious isotope dilution strategy, but more recently it has been possible to measure the cAMP waves dynamically using dedicated FRET constructs [87,88]. Interesting questions that can now be started to be resolved are what is the exact mechanism of cAMP amplification in single cells?…”
Section: Aggregationmentioning
confidence: 99%
“…These studies revealed useful information on cell migration, but because in general the relevant interactions in a social context and their relative importance are not established, migratory behavior of cells in a social context remains as one of the major unresolved problems in biology (30). Furthermore, striking social effects such as highly sensitive collective responses in a number of sensing systems [e.g., quorum sensing (31,32) and onset of collective behavior in Dictyostelium discoideum (33)] mediated by increased levels of cell-secreted signals in higher cell density indicate that mechanical links are not necessary for collective behavior. At the subcellular level, many types of nonswimming motile cells involved in multicellular biology [e.g., fibroblasts, Dictyostelium, and neutrophils (13,14,(16)(17)(18)] have been found to transmit traction force to the substrate by intracellularly polymerizing their cytoskeletons in dynamically formed membrane protrusions known as pseudopodia.…”
mentioning
confidence: 99%
“…It requires an excitable medium that locally amplifies a chemical state so the state can propagate through the medium faster than diffusion. Familiar examples include the Belousov-Zhabotinsky reaction [5], action potential in neurons [6], calcium waves during fertilization [7] and cAMP waves in a population of Dictyostelium cells [8,9]. Microtubule organization and cell cycle progression are not normally considered as chemical waves, apart from a few notable exceptions [10 -13].…”
Section: Introductionmentioning
confidence: 99%